The amazing days of abby hayes - Anne Mazer (USA Scholastic, 2000)
When Abby is told that she can't go to the Fall Festival with her friends, she becomes determined to show her parents how mature she has become by cleaning the house and taking care of her brother.
Keywords: Realistic Fiction -- Realistic Fiction